Phytochemical Profile and Pharmacological Mechanisms of Pandanus tectorius Fruit: A Comprehensive Review - Setiani, Lusi Agus; Herlina, Nina; Wahyuningrum, Cyntia; Putri, Nabilah Yuliana (Jurnal Jamu Indonesia, 2025)
The fruit of Pandanus tectorius, commonly known as screw pine or sea pandan, contains various secondary metabolites with significant therapeutic potential but remains underutilized in clinical applications. This review summarizes findings from 2014 to 2025 regarding its phytochemical composition and pharmacological effects. Sixteen bioactive compounds have been identified, including pandanusin A, bergapten, scoparone, scopoletin, several lignans, isoamericanin A, kaempferol, chrysin, phenolic acids, betulinic acid, and β-sitosterol. These constituents demonstrate antioxidant, anti-inflammatory, analgesic, antidiabetic, antimicrobial, and anticancer activities. Mechanistic actions include inhibition of alpha-glucosidase, reduction of oxidative stress, and induction of cytotoxicity in cancer cells. The ethyl acetate fraction, in particular, exhibits strong activity against HeLa cells. Novel delivery systems, such as nanoemulsions, are being explored to enhance solubility and bioavailability. Additionally, preclinical studies suggest roles in immune modulation, wound healing, and pain relief. Although promising, further clinical validation and formulation standardization are needed. This review highlights the potential of P. tectorius fruit as a candidate for evidence-based phytotherapeutic development.